(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2024)
Cardiac remodeling is a significant issue involving molecular, cellular, and interstitial changes that affect the size, mass, integrity, and function of the heart following a myocardial infarction (MI). We hypothesized that therapy with mixed herbal extracts has a protective effect in mouse models of MI. The underlying mechanisms are thought to be protective against left ventricular (LV) remodeling through reduced collagen deposition. We therefore studied the effects of mixed herbal extracts commonly used in various ways in the belief that they have beneficial effects on cardiac disease. MI was induced by left anterior descending (LAD) coronary artery ligation in switch albino mice. Ethanol extracts of herbs Arjuna bark, oleander leaves, ginseng root, garlic, cardamom seeds and oregano leaves were prepared by ethanol extraction and rotary evaporation technique of dried herbs and then mixed the extracts to make a therapeutic cocktail. The mixture is then administered orally by lavage for 28 days. At the end of 28 days cardiac tissues were harvested and stored for histopathology analysis and assessment of SOD levels. Survival curve data over a period of 28 days showed significant (P<0.05) differences between groups and mortality was reduced in the herbal extract treated group. Heart mass especially ventricular and atrial space and ratio of ​​infarct to total heart area revealed better improvement in treated group compared to untreated group. Histopathological studies showed that the myocardium of the herbal extract treated group had fewer collagen fibers than the non-treated group. SOD activity levels were up-regulated in animals treated with herbal extracts indicating reduction of oxidative stress by herbal extract mixture. Hence, their effects reduce collagen deposition, reduce LV mass and prevent myocardial tissue damage, reduce structural changes and increase survival by their anti-stress effects. Mixed herbal tonic may provide a new therapeutic approach in ischemic cardiomyopathy and ischemic heart failure. Asian Australas. J. Biosci. Biotechnol. 2024, 9(2), 14-23